Role of Human Resource Management in Improving Performance of Employees PDAM Tirtasari Binjai - Salman Firdaus; Muhammad Isa Indrawan; Suwarno (CERED Indonesia Institute, 2022)
This study aims to examine the role of human resource management in improving employee performance CV. Mitra Jaya Bersama banjarbaru and how human resource management in PDAM Tirtasari Binjai according to management's economic perspective. The data analysis used in this study is to use qualitative methods by means of library research, interviews, and documentation conducted at the research object. The results of this study aim to determine that the role of human resource management is very influential in improving the performance of employees of PDAM Tirtasari Binjai, and also to find out how to improve performance by using the role of human resource management, and to find out how human resource management in the Pdam Tirtasari Binjai according to management's economic perspective.